Detection of infection and determination of biomarkers for brucella melitensis infection in goats - Al-Garadi, Maged Ahmed Muthanna (2011)
Brucellosis is a chronic disease caused by Brucella spp. Brucella melitensis is one of the species of bacteria that infects animals and humans leading to undulant fever. The interaction between B. melitensis and immune system of the host could guide us towards the discovery of new biomarker to detect the infection as early as possible particularly understanding the unique pathway of B. melitensis and the intracellular features. In this study, 288 samples of whole blood and serum were collected from a goat farm in Kedah, Malaysia, which was suspected to have been affected by brucellosis. Serological and molecular detections of brucellosis were performed, using Rose Bengal Plate Test (RBPT), Complement Fixation Test (CFT), conventional PCR and real-time PCR (RT-PCR). Each test was evaluated with respect to its sensitivity and specificity ensuring that the recommendations made are able to be use for the national brucellosis eradication program in Malaysia. Isolation and identification of B. melitensis were also done in addition to conventional PCR and real-time PCR to detect B. melitensis from samples collected from vaginal swabs. CDs markers and its combination in different population of peripheral blood mononuclear cells (PMNC) were measured in detail, in different B. melitensis stages of the infection and in experimentally infected mice and goats by using specific monoclonal antibody. Histopathological picture was also been described in current study. The sensitivity of RBPT was 89.04% whilst CFT was 97.02%. The specificity of each of RBPT and CFT were 99.06% and 96.38% respectively. Four (4) B.melitensis isolates were isolated from 300 vaginal samples and all isolate belonged to B. melitensis biotype 1. The real-time PCR was the easier and safer method for the confirmation of brucellosis in goat’s population. The CDs biomarkers namely; CD14, CD4, CD25 markers were identified as good markers for the different stages of B. melitensis infection. A combination of a serological test namely RBPT and molecular technique, in particular real-time PCR based on the IS711 region of a hypothetical protein, showed promising results. This combination can be used to reduce the number of false positive results, which can cause severe economical loss during the implementation of proposed eradication programs.